Relationship between Formula Milk and the Incidence Obesity in Children Under Five: Meta-Analysis - Yopiana, Elma; Dewi, Yulia Lanti Retno; Murti, Bhisma (Indonesian Journal of Medicine, 2020)
Background: Obesity is a nutritional disorder that most often occurs in children. Obesity is associated with worse health outcomes in children, including asthma and sleep apnea. This study aimed to examine the relationship between formula feeding and obesity in children under five.Subjects and Method: This was a meta-analysis study conducted by systematically reviewing articles from PubMed, Science Direct, Springer Link, and Google Scholar. The articles used in this research are articles that have been published from 2008-2016. The search for articles was carried out by considering the eligibility criteria using the PICO model, P: toddlers, I: formula feeding, C: breastfeeding, O: obesity. The key words for finding articles were as follows: "OR" Formula milk "OR" Infant Formula") AND" Breast Feeding "AND (Obesity OR" Body Mass Index"). The inclusion criteria used were full paper, used English, cohort and cross-sectional observational study design and the results reported were adjusted odds ratio. Articles were collected using PRISMA diagrams, and analyzed using the Review Manager 5.3 application.Results: A total of 9 articles were conducted meta-analysis in this study with a sample size of 26,119. The results of the meta-analysis of the cohort study showed that formula feeding increased the incidence of obesity in children under five (aOR= 1.10; 95% CI= 0.78 to 1.56; p= 0.570). The results of the meta-analysis of cross-sectional studies showed that formula feeding increased the incidence of obesity in children under five (aOR= 1.25; 95% CI= 0.59 to 2.63; p= 0.560).Conclusion: Formula feeding increases the incidence of obesity in children under five.Keywords: Obesity, formula, toddlers, meta-analysisCorrespondence: Elma Yopiana. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email:  elmayopiana@gmail.com.Indonesian Journal of Medicine (2020), 05(04): 299-307https://doi.org/10.26911/theijmed.2020.05.04.05.